Chinese-to-English translation of political discourse: a feature-oriented analysis - Sun, Aina; Ng, Chwee Fang; Subramaniam, Vijayaletchumy; Abdul Ghani, Che Ann (Arab World English Journal, 2022)
The translation of political discourse differs from the translation of texts in non-political contexts in which political discourse is highly profiled in terms of political sensitivity and policy orientation. It may potentially influence global peace and security. Understanding the features of translating China’s political discourse from Chinese to English is of great help to political translators and researchers in studying the problems and strategies of political translation for attaining the above expectation. It is expected to help the international community understand clearer and better the stance, response, and policies adopted by the government in national and international affairs. Therefore, the translation of China’s political discourse should deliver the intended information accurately and adequately the national characteristics of the source text and conduct flexible adjustments to conform to the language habits and ways of thinking of the target audience while mainlining the correct political position. This article aims to review and identify the essential characteristics of translating China’s political discourse from Chinese to English. It is apparent in understanding the desired political translation effect and some relevant translation problems. The bibliometric research method concludes that the Chinese-to-English translation of China’s political discourse has four distinctive features: accuracy, international-audience-centeredness, national characteristics, and political rightness. It is recommended that the translator pay great attention to these features while selecting translation strategies and methods and raise the acceptability of the translated text among the global recipients for promoting an authentic national image of the country.